Protective Effect of Litchi chinensis Peel Extract-Prepared Nanoparticles on Rabbits Experimentally Infected with Eimeria stiedae - Dina M. Metwally; Afrah F. Alkhuriji; Ibrahim A. H. Barakat; Hanadi B. Baghdadi; Manal F. El-Khadragy; Wafa Abdullah I. Al-Megrin; Abdullah D. Alanazi; Fatemah E. Alajmi (Animals, 2022)
The present study used Litchi chinensis peel extract to synthesize silver nanoparticles (AgNPs). This technique is eco-friendly and can be performed in a single step; thus, it has attracted great attention for NPs biosynthesis. Herein, we biosynthesized AgNPs with L. chinensis peel extract and examined their anticoccidial activity in rabbit hepatic coccidiosis induced by E. stiedae infection. Thirty-five rabbits were allocated into seven groups: a healthy group (G1), an infected control group (G2), four groups infected before treatment with 10 mg/kg L. chinensis peel extract-biosynthesized AgNPs (G3, G5) or 50 mg/kg amprolium (G4, G6), and rabbits infected after two weeks of pretreatment with 10 mg/kg L. chinensis eel extract-biosynthesized AgNPs (G7). In this study, both pre-and post-treatment with AgNPs produced a substantial reduction in fecal oocyst output, liver enzyme levels, and histopathological hepatic lesions relative to the infected group. In conclusion, L. chinensis peel extract-prepared AgNPs should be considered harmless and efficient in the cure of hepatic coccidiosis in rabbits.